2020
DOI: 10.1002/ijc.33265
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy after breast‐conserving surgery for elderly patients with early‐stage breast cancer: A national registry‐based study

Abstract: Considerable controversies exist regarding whether elderly patients with early-stage breast cancer receiving breast-conserving surgery (BCS) should forgo radiotherapy. We utilized the National Cancer Database to analyze data of 115 516 women aged ≥70 years, treated with BCS for T1-2N0-1M0 breast cancer between 2004 and 2014. Multivariable Cox proportional hazards model was used to estimate hazard ratios (HR) and 95% confidence intervals (CI) for mortality 3, 5 and 10 years after 90 days of BCS associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Although high-quality evidence exists, the relatively short follow-up time and limited statistical power limit the results of prospective randomized trials for clinical practice. Studies with longer follow-up are required to detect significant differences in OS, but it is worth emphasizing that large retrospective population based-studies including ours have found early differences in OS ( 11 , 12 , 30 ). The large population-based studies not only provided real-world clinical evidence but may also compensate for any retrospective design-related drawbacks.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Although high-quality evidence exists, the relatively short follow-up time and limited statistical power limit the results of prospective randomized trials for clinical practice. Studies with longer follow-up are required to detect significant differences in OS, but it is worth emphasizing that large retrospective population based-studies including ours have found early differences in OS ( 11 , 12 , 30 ). The large population-based studies not only provided real-world clinical evidence but may also compensate for any retrospective design-related drawbacks.…”
Section: Discussionmentioning
confidence: 79%
“…However, it should be noted that early patient enrollment, imprecise RT techniques, and insufficient endocrine therapy may impact the survival benefit of RT. Recently, two studies from the National Cancer Database (NCDB) showed a positive impact of RT in this population, they found that RT could improve the OS of patients, especially for those treated with endocrine therapy and RT ( 11 , 12 ). However, the NCDB does not record BC-related deaths in patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these findings, the U.S. national guidelines recommended omitting adjuvant radiotherapy after BCS for EBC women 70 years of age and older who are prescribed endocrine therapy [ 9 ]. However, whether radiotherapy is beneficial in the elderly is still a matter of debate, with results of recent studies using observational real-world data reporting higher mortality rates in those who did not receive radiotherapy after BCS [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%